Child Self-Report Measures of Primary-Secondary Transition Experiences and Emotional Wellbeing: An International Systematic Literature Review - Bagnall, Charlotte Louise; Jindal-Snape, Divya (International Journal of Educational and Life Transitions, 2023)
A systematic literature review of international empirical research was conducted to examine what child self-report measures have been used to assess their primary-secondary school transitions experiences and/or emotional wellbeing. The systematic review covered the period 01/2008 and 03/2021 with the aim of (a) understanding authors’ conceptualisation of primary-secondary school transitions and emotional wellbeing, and (b) systematically reviewing transitions and emotional wellbeing scales used in primary-secondary transitions research.Using the EPPI-Centre (2010) method, after a rigorous screening of 4,518 records, 60 articles were included based on the study’s inclusion/exclusion criteria. Synthesis of the findings identified that the corpus of measures used to date to assess primary-secondary school transitions and/or emotional wellbeing have the following key limitations: 1. do not take into account the longitudinal and dynamic nature of primary-secondary school transitions and emotional wellbeing, 2. use negative terminology, 3. use inaccessible formats (e.g. broad number of items), 4. do not assess both transitions and emotional wellbeing in a single scale, 5. inconsistent reliability and validity assessment (especially when measures are adapted) and 6. key constructs (transitions and emotional wellbeing) are not conceptualised and/or theoretically defined. Lack of understanding of these limitations could negatively impact transitions research, and lead to policies and practices that are not fit for purpose, in turn having a negative impact on children’s emotional wellbeing.This is the first systematic literature review to focus on the use of emotion wellbeing scales in the context of primary-secondary transitions and concludes with several original and significant implications for future research, policy and practice.
Keywords: emotional wellbeing; primary school; secondary school; school transitions; measures